Simulation of Shariah compliant commodity backed currency system: a Turkish case-study - Ahmed, Jameel; Collins, Patrick; Mydin Meera, Ahamed Kameel (Research Centre Islamic Economics (IKAM), 2018)
In view of the continuing episodes of financial crises faced by the Turkish economy, this study analyses the potential economic benefit of implementing the Grondona system of conditional currency convertibility. The authors performed simulations of the Grondona system based on Grondona's guidelines (1975) in order to examine the impact of the system's operations on the Turkish economy. For simulations, the annual data about Turkish primary commodity imports was retrieved using the WITS (World Integrated Trade Solution) software developed by the World Bank. The monthly data about primary commodity prices was accessed from the IndexMundi website. The authors used a program developed in C++ for performing simulations, and analyzed the simulation results by using Microsoft Excel. The results of the simulations clearly show the system's role in stockpiling reserves of primary imported commodities in response to a fall in market prices, and releasing the reserves during periods of rising prices. Such a mechanism helps to stabilise the prices of primary commodities and lessen the pressure on primary commodities markets during both slump and boom periods. Graphs are also included to show how the Commodities Reserve Department's (CRD) transactions would have caused corresponding changes in the Turkish money supply. These would have a stabilizing influence on the real value of the Turkish Lira in terms of the commodities handled. In addition the paper discusses the multiple reasons why the system has been judged to be Shariah-compliant.